2007
DOI: 10.1117/12.728996
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of litho printability of DRAM contact hole patterns with various programmed defects

Abstract: As the photomask design rules continue to shrink towards 45nm and below, the defect classification criteria is becoming more challenging to be set accurately. Pattern fidelity issues and masks defects that were once considered insignificant or merely nuisances are now yield-limiting. On the other hand, there are still cases of small defects captured during reticle inspection but will not print on the wafer. In addition, in a production setting environment it is critical to ascertain quickly and efficiently the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Paper has shown that AMDD can give CD results that are consistent with AIMS after quantification and calibration of their image intensity difference [3,5]. AMDD is based on PROLITH, which is a CD calculation software using inspection image from KLA-Tencor Co. inspection tools.…”
Section: Automated Mask Defect Disposition (Amdd)mentioning
confidence: 90%
“…Paper has shown that AMDD can give CD results that are consistent with AIMS after quantification and calibration of their image intensity difference [3,5]. AMDD is based on PROLITH, which is a CD calculation software using inspection image from KLA-Tencor Co. inspection tools.…”
Section: Automated Mask Defect Disposition (Amdd)mentioning
confidence: 90%